Evaluation of The Training Team Development Program DKI Jakarta Men's Rugby at Pon XX Papua 2021 - Andre Fiksi Gumilang; Tirto Aprianto; Sri Nuraini; Oman Unju Subandi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to evaluate the context, input, process and product components in the DKI Jakarta men's Rugby Training Team coaching program in 2021. Evaluation research with the CIPP model uses qualitative methods. The subjects of this study are the coaching components of Achievements, Athletes, and Coaches. The results show that the context evaluation in the DKI Jakarta Rugby Training Program is included in the very good category (100%). In the input component, it is stated that it is very good 100% visible from, All athletes' conditions have been met, namely, Meeting the age criteria of 18+, Physical and spiritual health meeting body posture qualifications (anthropometric), Meeting the criteria for Rugby cabor skills, Meeting physical capacity standards, Meeting psychological criteria, Meeting health criteria. Have dormitory / TC equipment, Training equipment, Sparring equipment. In the Process component, decision making is very good (100%), the supervision process is also very good (100%), but the monintoring process is included in the less category (50%). In the Product component, the results of the men's team coaching program for the Dki Jakata Men's Rugby Rugby Team at PON XX Papua 2021 won a silver medal but did not match the targets and expectations that had been made for the Dki Jakata Men's Rugby Team coaching program at PON XX Papua 2021. Based on the things mentioned above, the results of the men's team coaching program of the Dki Jakata Men's Rugby Team coaching at PON XX Papua 2021 are included in the category of very less (0%). Based on the results of the evaluation component research above, the coaching program of the Dki Jakata Men's Rugby Team at PON XX Papua 2021 as a whole obtained a value of 70.83%. So it can be concluded that the coaching program of the Dki Jakata Men's Rugby Team at PON XX Papua 2021 is considered good.